Taxonomic revision of Cumbre Evans, 1955 (Hesperiidae: Hesperiinae: Moncini), with the description of two new species - Dolibaina, Diego Rodrigo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2014)
The genus Cumbre Evans, 1955 (Hesperiidae: Heperiinae: Moncini) and its respective species are revised. Two new species are described, Cumbre haywardi sp. nov. from Peru and Argentina (type locality) and Cumbre lamasi sp. nov. from Ecuador and Peru (type locality). A lectotype for Phanis cumbre Schaus, 1902 is designated. The examination of the Phanes triumviralis Hayward, 1939 and Phanes belli Hayward, 1939 holotypes indicates that these taxa are new synonyms (n. syn.) of Poanes meridionalis Hayward, 1934, which is a valid species (stat. rev.).